Pengaruh Media Poster Terhadap Peningkatan Pengetahuan, Sikap Dan Tindakan Guru Dalam Pemberian Imunisasi Campak Rubella Pada Murid Sekolah Dasar Di SD It Al Wahdah Kendari Tahun 2023 - Siska Wulandari; Hartati Bahar; Kamrin Kamrin (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2024)
Immunization is one of the measures to prevent the spread of disease in other areas which has been proven to be very cost effective. Measles rubella is a disease that can be transmitted through the air, namely when a sufferer sneezes or coughs. This disease can attack toddlers and children aged 9 months to 15 years, causing them to suffer from hearing loss, cataracts, speech delays and heart failure. This research aims to determine the effect of poster media on increasing knowledge, attitudes and actions of teachers in providing measles rubella immunization to elementary school students at SD It Al Wahdah Kendari in 2023. The research method used is a quantitative approach, pre experimental design type with research design one pre test-post test group. The research sample was 33 people using a total sampling technique. The instruments used in this research were questionnaires and posters. The results of this research show that the p-value of the Wilcoxon test for knowledge is 0.000, the attitude p-value is 0.000 and the action p-value is 0.000. It can be concluded that there is an influence of poster media on increasing teacher knowledge, attitudes and actions in providing measles rubella immunization because the p-value is <0.000.